Immigration Policy and Remittance Behaviour - Matloob Piracha; Massimiliano Tani; Guy Tchuente (Global Labor Organization (GLO), 2021)
This paper analyses the remittance behaviour of two cohorts of migrants who entered Australia before and after a policy change implemented in the 1990s, which tightened the entry requirements for a subgroup of applicants. We use a mix of a conditional difference-in-differences and OLS estimator accounting for the presence of interactive fixed-effects to address the challenge of evaluating the impact of policy change using data drawn from two distinct migrant samples, deriving the conditions to obtain a consistent estimator. We show two results: one due to policy change and the other due to change in the composition of migrants. The two results capture different aspects of remittance behaviour.
Keywords: C13; F22; F24; J61; 330; Immigration; average treatment effect on the treated; difference-in-differences